Conservative management of cicatrix after circumcision: Retraction and steroid - Ekber Hakalmaz, Ali; Huseynov, Mirzaman (Annals of Medical Research, 2021)
Aim: Our study aims to study the combined manual retracting and topical steroid application method for the treatment of post-circumcision cicatrix in neonates and infants and to establish the need for a secondary intervention. Material and Methods: A total of 20 patients applying to our clinic with post-circumcision cicatrix between April 2018 and January 2019 were evaluated retrospectively. Multivariable analyses assessed the association between the age of the patients and the onset of complaints associated with cicatrix, the time to onset of symptoms, and the duration of recovery.Results: The mean age at admission was 7.8 months (4-13 months), and the mean age at circumcision was 3.4 months (2 weeks-6 months). In our study, all the patients had been fully recovered after the treatment with combination of topical 0.1% betamethasone ointment and manual retraction. The mean duration of treatment was 30.6 days (14-56 days). Conclusion: In this study, we reported our observations related to the treatment only with 0.1% Betamethasone ointment and manual retraction for the first time in the literature. We believe that before choosing secondary applications which potentially traumatize the patient, insisting on topical steroid and manual retraction will provide a satisfactory outcome.